El problema contextual como estrategia didáctica en el aprendizaje de la caída libre de los cuerpos en los estudiantes del primer año de bachillerato general unificado, de la unidad educativa Hno. Ángel Pastrana Corral de Loja, periodo 2015-2016 - Guaicha Saetama, Adrián Guillermo (2017)
The present investigation refers to the Contextual Problem like didactic strategy in learning of free fall of the bodies in the students of the first year of Baccalaureate General Unificado, of the Educational Unit Hno. Ángel Pastrana Corral of Loja, period 2015-2016. Ittakes as a target to make use of the Problem Contextual to promote learning of the free fall of the bodies. To give ful fillment to this target the investigation he answered to a design with descriptive base and of type preexperimentally, be applied one the following phases in its order: comprehensive, of diagnosis, of modeling, workshop and the evaluation across the test Sealed Status of Wilcoxon. The planning applied with the strategy of the Problem Contextual provides the necessary elements to promote learning, since a climate harmonious is garantice and adapted to analyze, to interpret and to discussdaily situations where the student more of to relate with what already knows robustece its cognitive capacities, skill sand work manship. The Problem Contextual is the resource tomitigate the cognitive short comings, skills and competitions of the free fall oft he bodies